THE CURRENT STATE AND DEVELOPMENT TRENDS OF THE QUALITY OF PRIMARY EDUCATION IN THE UK AND THE USA - Ruzmetova Novval Vahabdjanovna; Shoakmalova E’zoza Alisherovna (Bright Mind Publishing, 2026)
This article examines the current state and development trends of the quality of primary education in the United Kingdom and the United States. It focuses on key dimensions such as curriculum standards, teaching quality, assessment and accountability systems, and educational equity. Using a comparative qualitative research approach, the study analyzes official government policies, national education reports, and international assessment data published by recognized educational organizations. The findings indicate that although both countries have implemented significant reforms aimed at improving primary education quality, notable differences remain in governance structures and policy implementation. The centralized curriculum framework in the United Kingdom supports consistency in educational standards, while the decentralized system in the United States allows flexibility but contributes to variation in educational quality. Furthermore, persistent socio-economic inequalities and unequal access to educational resources continue to influence learning outcomes. The article highlights the importance of balanced educational policies, continuous teacher professional development, inclusive educational practices, and equitable resource allocation to ensure sustainable improvement in the quality of primary education in both countries.
Keywords: Primary education, educational quality, curriculum reform, United Kingdom, United States, comparative education.